Prevalence of binge drinking and associated behaviours among 3286 college students in France - Marie-Pierre Tavolacci; Eloïse Boerg; Laure Richard; Gilles Meyrignac; Pierre Dechelotte; Joël Ladner (BMC, 2016)
Abstract Background Studies conducted on characteristics of binge drinking and associated behaviours in college student populations are scarce especially in France. Hence, it is important to identify risk factors for binge drinking at university, especially those which may be changed. The aim of this study was to assess the prevalence of binge drinking and associated behaviours across a large sample of college students in Upper Normandy (France). Methods A cross sectional study was performed between November 2009 and February 2013 and data on socioeconomic characteristics and behavioural risk factors were collected: alcohol (consumption and misuse of alcohol, occasional and frequent binge drinking), tobacco, cannabis, cyberaddiction, stress and depression. An anonymous self-administered questionnaire was filled out by college student volunteers from Upper Normandy (France) either online or by paper questionnaire. Analyses were performed using multivariate logistic regression models. Results A total of 3286 students were included. The mean (Standard Deviation (SD)) age of students was 20.8 years (SD = 2.1) with a male-female ratio of 0.60. The prevalence of binge drinking in the never, occasional and frequent categories was respectively 34.9 %, 51.3 %, and 13.8 %. The mean number of units of alcohol consumed per week (except BD episodes) was 0.78 for never, 3.7 for occasional and 10.5 for frequent binge drinkers (p < 0.0001). A positive relation was observed between frequent binge drinking and the following: male gender (AOR 4.77 95 % CI (3.43-6.63); p < 0.0001), living in rented accommodation AOR 1.70 95 % CI (1.21-2.40; p < 0.0001), attending business school AOR 4.72 95 % CI (2.76-8.08; p < 0.0001), regular practice of sport AOR 1.70 95 % CI (1.24-2.34; p = 0.001), smoking AOR 5.89 95 % CI (4.03-8.60; p < 0.0001), occasional cannabis use AOR 12.66 95 % CI (8.97-17.87;p < 0.0001), and alcohol abuse AOR 19.25 95 % CI (13.4-27.72; p < .0001). A negative association was observed between frequent binge drinking and grant holder status, living in couples, and stress. Conclusions This study highlights the spread of binge drinking among college students and identifies student populations at risk: male gender, living in rented accommodation, regular practice of sport, and other risk behaviours such as use of tobacco, cannabis and alcohol. These behaviours increase with the frequency of binge drinking.